The Relationship Between Emotional Intelligence and Sales Executives' Performance: Investigating the Impact of Emotional Intelligence on Sales Performance (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The present study explained the relationship between theemotional intelligence and the performance of the sales executives weredirectly selling to the end user and the universe excluded sales executivesbelonging to the group of channel salesmen or missionary salesmen. Executiveswho were selling products to the industrial buyers alone and executives who weredoing telemarketing were also excluded. Further research may be initiated toconfirm the El-Performance relationship among such group of sales executives sothat the present findings would become generalizable among all groups of salesexecutives. The researcher could not explain the relationship between theswitchovers of the sales executives from company to other companies in terms oflow emotional intelligence. This is not in confonnity with the findings of someother researchers. If further research is conducted among a sample that arehaving larger years of experience and career history of more frequentswitchover may bring out more accurate results. The present sample consistedmore of youngsters and number of switchover was a few in majority of the cases.Overall emotional intelligence of the sales executives had been measured anddid not undertake any micro analysis on effects of various components of El onperfonnance.